2019
DOI: 10.1016/j.pacfin.2019.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Is informational inefficiency priced in stock markets? A comparison between the U.S. and Chinese cases

Abstract: Using a sample of U.S. and Chinese stocks between July 1999 and June 2016, we investigate the pricing role of informational inefficiency in stock markets. We find that the relations between returns and the informational inefficiency factor statistically change from significantly positive, to insignificant, and further to significantly negative as informational efficiency increases. This finding provides new insights into the common belief that emerging markets are less efficient than developed markets. We prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…In addition, other results show that the company's performance, as represented by ROE, also has no effect on stock price crash risk. We find that information inefficiency results in general distrust of stock markets in developing countries (Yang et al , 2019). Information inefficiency is a global problem that always exists in the stock market, although more prevalent in developing countries than developed countries (Boya, 2019; Bartram and Grinblatt, 2021).…”
Section: Discussionmentioning
confidence: 80%
“…In addition, other results show that the company's performance, as represented by ROE, also has no effect on stock price crash risk. We find that information inefficiency results in general distrust of stock markets in developing countries (Yang et al , 2019). Information inefficiency is a global problem that always exists in the stock market, although more prevalent in developing countries than developed countries (Boya, 2019; Bartram and Grinblatt, 2021).…”
Section: Discussionmentioning
confidence: 80%
“…Comparing developed and emerging markets, Jiang and Li [147] indicated that the Japanese and US stock exchanges are efficient in the normal market condition, while Chinese market was found to be generally inefficient. Conversely, Yang et al [148] suggest that US and Chinese stock markets are adaptive.…”
Section: Time Varying Efficiency Studiesmentioning
confidence: 98%
“…at is, information efficiency can be the basis of market price efficiency, and the measurement of information efficiency is theoretically a test of market efficiency. But in developing economies' financial markets, due to the high appearance of false transactions and falsified financial data, some traditional models are not effective in studying these markets [5]. Since in markets, a transaction is a transaction, and the data that appear every moment bring useful information; therefore, this study looks forward to considering the problem in a purely data-driven way.…”
Section: Introductionmentioning
confidence: 99%